Diverse regulatory factors associate with flowering time and yield responses in winter-type Brassica napus - Schiessl, Sarah; Iniguez-Luy, Federico; Qian, Wei; Snowdon, Rod J.; Justus Liebig University Giessen (My University, 2015)
Background: Flowering time, plant height and seed yield are strongly influenced by climatic and day-length adaptation in crop plants. To investigate these traits under highly diverse field conditions in the important oilseed crop Brassica napus, we performed a genome-wide association study using data from diverse agroecological environments spanning three continents. Methods: A total of 158 European winter-type B.napus inbred lines were genotyped with 21,623 unique, single-locus single-nucleotide polymorphism (SNP) markers using the Brassica 60 K-SNP Illumina® Infinium consortium array. Phenotypic associations were calculated in the panel over the years 2010 2012 for flowering time, plant height and seed yield in 5 highly diverse locations in Germany, China and Chile, adding up to 11 diverse environments in total. Results: We identified 101 genome regions associating with the onset of flowering, 69 with plant height, 36 with seed yield and 68 cross-trait regions with potential adaptive value. Within these regions, B.napus orthologs for a number of candidate adaptation genes were detected, including central circadian clock components like CIRCADIAN CLOCK- ASSOCIATED 1 (Bna.CCA1) and the important flowering-time regulators FLOWERING LOCUS T (Bna.FT) and FRUITFUL (Bna.FUL). Discussion: Gene ontology (GO) enrichment analysis of candidate regions suggested that selection of genes involved in post-transcriptional and epigenetic regulation of flowering time may play a potential role in adaptation of B. napus to highly divergent environments. The classical flowering time regulators Bna.FLC and Bna.CO were not found among the candidate regions, although both show functional variation. Allelic effects were additive for plant height and yield, but not for flowering time. The scarcity of positive minor alleles for yield in this breeding pool points to a lack of diversity for adaptation that could restrict yield gain in the face of environmental change. Conclusions: Our study provides a valuable framework to further improve the adaptability and yield stability of this recent allopolyploid crop under changing environments. The results suggest that flowering time regulation within an adapted B. napus breeding pool is driven by a high number of small modulating processes rather than major transcription factors like Bna.CO. In contrast, yield regulation appears highly parallel, therefore yield could be increased by pyramiding positively associated haplotypes.
Keywords: GWAS; rapeseed; population structure; post-transcriptional regulation; SNP marker; ddc:630